Victimizations of Mexican youth (12–17 years old): A 2014 national survey. (May 2017) - Frías, Sonia M.; Finkelhor, David
Abstract: Victimization of Mexican youth (aged 12–17) has received little attention compared to that of adults. Using the 2014 Social Survey on Social Cohesion for the Prevention of Violence and Delinquency, we examine prevalence and types of victimization; describe the characteristics of incidents in terms of relationship with perpetrator(s) and places where took place; and study significant correlates of forms of victimization and poly-victimization. During 2014 alone, more than 2.8 million minors were victims of bullying, cyberbullying, theft, sexual abuse, physical assault, threats, robbery, or extortion. About 10% of these were poly-victims-experienced at least four different types of victimization by at least four types of perpetrators. Youth tended to be victimized by people in their inner circle. The factors associated with victimization tended to vary by victimization type, but proximity to crime and peer delinquency increased the risk of experiencing all types of victimization. Implications for future research and practice are discussed.